The SAGE handbook of emotional and behavioral difficulties. - Garner, Philip, 1947-; Kauffman, James M.; Elliot, Julian (SAGE, 2013)
This important revision with updated material will inform professionals, students, and the interested public of evolving international perspectives on EBD. New chapters consider causation, the influence and role of social contexts and social support, ADHD, teacher knowledge and parental engagement. The new content presents us with fresh ideas and approaches.' - Katherine Bilton, University of Alaska, USA This new edition of The Handbook of Emotional and Behavioural Difficulties, first published in 2004, has been completely reworked and refreshed by a new editorial team led by Philip Garner. A thorough revision of existing content, together with new material, bring the volume firmly up-to-date, and offers guidance and recommendations for future research and practice.- Resumé vydavatel
Previous edition: published as Handbook of emotional & behavioural difficulties. 2005.
Keywords: problémové děti; vzdělávání; poruchy chování; problem children; education; behavioral disorders; elektronické knihy; příručky; electronic books; handbooks and manuals